Reasons of individuals to trust what they read on social network sites - Sander, T.; Teh, Phoey Lee * (Springer, Cham, 2021)
The rationality of believing a piece of information depends on the level of trust of each individual. To make a purchase decision, an individual has to trust the information they have collected from social media content. That said, to influence an individual’s decision, companies have to obtain an individual’s trust successfully. This study aims to investigate what makes an individual trust what they read on social media (SM). Participants of this study are from Germany and United Kingdom (UK). A model is created and tested with regression analysis. That helps to identify the impact experience with social network sites (SNSs) on trust of information in SNSs. The practical outcome is to provide advice to companies whereby to communicate with potential clients to transfer their information successfully and trustworthy.